Інтегроване навчання як засіб оптимізації освітньо-виховного процесу в сучасному дошкільному закладі - Боярчук, Світлана (Східноєвропейський національний університет імені Лесі Українки, 2017)
У статті розглядається проблема організації інтегрованого навчання дітей дошкільного віку, яке є одним із дієвих засобів підвищення якості та інтенсифікації освітньо-виховного процесу у сучасному дошкільному закладі, розкривається сутність поняття «інтеграції». Інтеграція є однією з освітніх перспектив, у якій закладені оптимальні умови діяльності. problem of organization of integrated education of preschool children, which is one of the most effective means of improving the quality of education and intensification of educational process in modern preschools, the essence of the concept of integration. Integration is one of the educational prospects, which incorporated the optimal conditions of activity. Due to the integration of the content of preschool education child acquires knowledge not only of individual branches as integral knowledge about life, the world in which she lives. Applying the principle of integration significantly enhances the educational process, driven analytical and synthetic activity of children growing need for a systematic approach to the object of knowledge, forming ability to analyze, compare items, objects environment, providing a holistic perception of the world. It is able to form an integrated education a child of preschool age philosophy as a system of views on the environment, contribute to the formation in his mind the whole picture of the world, the formation of the child as an active subject of life, a competent person.
Keywords: інтеграція; інтегроване навчання; інтегрований підхід; інтегративні процеси; інтегроване заняття; цілісне сприйняття світу; оптимізація